Implementasi dan Modifikasi terhadap Pengakuan Asal-Usul Anak (Nasab) di Luar Nikah yang Sah Analisis Putusan Mk No.46/PUU-VIII/2010 - Millatul Hakimah; Dairani Dairani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
On February 17, 2012, the Constitutional Court granted the lawsuit filed by Hj. Aisyah Mochtar who filed a judicial review of Article 34 Paragraph (1) of Law Number 1 of 1974 concerning Marriage. This lawsuit arose from her marriage to Moerdiono in accordance with Islam which was not officially registered, which gave birth to a son, Iqbal Ramadhan. The Constitutional Court's decision changed the status of illegitimate children, who previously only had a civil relationship with the mother, now also have a civil relationship with the father and the father's family. This decision applies not only to children born from unregistered marriages, but also to children from relationships between men and women without the bonds of marriage which can be proven through technology such as DNA testing. These children are entitled to civil rights protection, such as maintenance and education, but are not related to guardianship issues. In its considerations, the Constitutional Court emphasized that the law must provide fair protection and legal certainty for the status of children, including those born even though their marriage is still disputed. Eliminating discrimination against illegitimate children aims to provide positive value for the future of children. The obligation of alimony that was previously only borne by the mother, is now shared with the father who can be proven to have a blood relationship with the child. If the father neglects to fulfill his obligations, he can be sued in court. The next question is how the Constitutional Court Decision will be implemented regarding the recognition of the lineage of children born outside of legal marriage.